Historical Traditions and Linguistic Analysis in the Interpretation of the Qur'an: Comparison of the Tafsir of Jawāhir al-Hisān and Ma'ālim at-Tanzīl - Anggun Puspita Ningrum; Muhammad Habib Izzudin Amin (al-Afkar, Journal For Islamic Studies, 2026)
The classical tradition of interpretation is rich in the diversity of methodologies developed by the mufassirs, especially in the form of summary writing. This research aims to compare the interpretation patterns of al-Baghawi and ats-Tsa'alibi in order to reveal unique characteristics, considering the status of these two works as a result of the transmission and summary of previous authoritative works. The focus of the study is directed at the interpretation of QS. al-Fatihah [1]: 2 which represents the typology of theological verses-praise, and QS. an-Nisa’ [4]: 34 which represents the typology of legal verses and social relations. This research uses comparative analysis methods, the results of the research show that al-Baghawi tends to use a moderate bi al-ma'tsur approach with a concise but history-intensive presentation. In contrast, Ats-Tsa'alibi highlights deeper integrative characteristics in linguistic, grammatical (i'rab), and contextual analysis, although it remains based on history. On the issue of nasyuz, both agree on the stages of the wife's education, but Ats-Tsa'alibi is more detailed in exploring linguistic meanings to provide preventive limits on injustice. This study contributes to the treasures of tafsir studies by mapping the transmission of classical commentators' scholarship as well as clarifying the methodological position of these two figures in Islamic intellectual history. This research confirms that the accentuation distinction between pure history approaches and linguistic-contextual analysis is not merely technical, but rather a mufasir response to the needs of different times.